Vulnerabilities in IoT Devices for Smart Home Environment - Costa, Luís (2019)
Recently, consumers have seen multiple products being advertised as smart home. These products promise to make our homes more comfortable, safe, automated, and remotely controlled. To this new reality of processing information it was given the name IoT (Internet of Things). Many news headlines have been published exposing serious security vulnerabilities in many IoT devices, with some of them being exploited to make one of the largest DDoS attacks recorded. In this paper we present a method developed with the purpose of identifying high risk vulnerabilities in smart home IoT devices, giving application examples of actual vulnerabilities found in two commercially available devices. This method uses several open source tools to identify vulnerabilities in some of these IoT devices. Besides, we will also present some topics related to the main threats and vulnerabilities that affect smart home IoT devices.